2024
DOI: 10.1177/17470218231220912
|View full text |Cite
|
Sign up to set email alerts
|

Concepts of order: Why is ordinality processed slower and less accurately for non-consecutive sequences?

Declan Devlin,
Korbinian Moeller,
Iro Xenidou-Dervou
et al.

Abstract: Both adults and children are slower at judging the ordinality of non-consecutive sequences (e.g., 1-3-5) than consecutive sequences (e.g., 1-2-3). It has been suggested that the processing of non-consecutive sequences is slower because it conflicts with the intuition that only count-list sequences are correctly ordered. An alternative explanation, however, may be that people simply find it difficult to switch between consecutive and non-consecutive concepts of order during order judgement tasks. Therefore, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In fact, it was demonstrated that distance and direction still explained unique variance in response times beyond the effect of familiarity. Likewise, these findings do not negate the possibility that a count-list bias contributes to order processing performance (but see Devlin, Moeller, Xenidou-Dervou, Reynvoet, & Sella, 2023).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…In fact, it was demonstrated that distance and direction still explained unique variance in response times beyond the effect of familiarity. Likewise, these findings do not negate the possibility that a count-list bias contributes to order processing performance (but see Devlin, Moeller, Xenidou-Dervou, Reynvoet, & Sella, 2023).…”
Section: Discussionmentioning
confidence: 75%
“…This effect is reversed relative to the standard distance effect observed in magnitude comparison tasks whereby judgments become faster as the numerical distance between compared digits increases (e.g., Moyer & Landauer, 1967;Sekuler & Mierkiewicz, 1977). However, viewing the reverse distance effect in order processing as analogous to the standard distance effect observed in magnitude processing has been discouraged (Devlin et al, 2022(Devlin et al, , 2023. This is because, instead of response times increasing linearly as the numerical distance between digits increases, the effect appears specific to distances of 1.…”
Section: Introductionmentioning
confidence: 90%